QUEST TECHNOLOGY AS A WAY OF SOCIAL AND CULTURAL ADAPTATION OF FOREIGN STUDENTS AT THE LESSONS OF RUSSIAN AS A FOREIGN LANGUAGE - Golovina, Lyubov; Molchanova, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The relevance of the article is determined by the need to define effective and relevant ways of acquaintance of foreign students with the realities of the new social culture, which will subsequently have a beneficial effect on the learning outcome. The purpose of the article is to systematically present ways of working with quest technology in foreign language classes, which are aimed at increasing the level of socio-cultural adaptation of foreign speakers in the new language and cultural community. The methodology of the present study is civilizational and cultural approaches, the work uses a logical method (theoretical), the study of the experience of educational organizations and personal pedagogical experience at the University (empirical).The author came to the conclusion that the modern educational process of training at the preparatory Department of the University should be aimed not only at achieving the necessary level of linguistic training, but also at the gradual systematic immersion of foreigners in a new socio-cultural environment through language. One of the most popular technologies in pedagogy is the quest that includes both solving a problem task and independent search for information. Educational quest in a foreign language at pre-University stage of education is the most effective, because it can be used at any level of language training, it perfectly solves the problem of language education and formation of speech culture, socio-cultural adaptation of foreign students in the conditions of the new region and explore the national cultural realities that undoubtedly contributes to a better understanding of internal and external communications companies.